2021
DOI: 10.1177/17479541211058579
|View full text |Cite
|
Sign up to set email alerts
|

Understanding female coaches’ and practitioners’ experience and support provision in relation to the menstrual cycle

Abstract: The study aimed to develop an understanding of female coaches’ and sport science practitioners’ experience and support provision in relation to the menstrual cycle when working with female athletes. Following receipt of institutional ethical approval, 14 female coaches and practitioners (32.9 ± 6.9 years) participated in individual semi-structured interviews. Following analysis, two themes were developed: (1) Knowledge and awareness and (2) Support and management. Overall, it appeared that participants varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…This is consistent with previous research which reported that many teachers felt embarrassed, potentially resulting from a lack of training received ( 20 ). Similar findings have been reported by Brown and Knight ( 39 ) within sport; the variation in female coaches' personal experiences of the menstrual cycle limited their overall understanding and awareness as their own experiences are not universal. This impacted on the support provided to female athletes, in combination with additional perceptions of secrecy relating to the menstrual cycle, reducing the informational and emotional support participants provided.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with previous research which reported that many teachers felt embarrassed, potentially resulting from a lack of training received ( 20 ). Similar findings have been reported by Brown and Knight ( 39 ) within sport; the variation in female coaches' personal experiences of the menstrual cycle limited their overall understanding and awareness as their own experiences are not universal. This impacted on the support provided to female athletes, in combination with additional perceptions of secrecy relating to the menstrual cycle, reducing the informational and emotional support participants provided.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, athletes', practitioners' and researchers' responses to cravings were almost always considered in relation to the performance narrative i.e., will this help me perform and/or in relation to the thin ideal i.e., will this help me control body mass. Additionally, both the sex and the underlying knowledge appeared to influence any support provided as has been previously demonstrated (Brown & Knight, 2022;Clarke et al, 2021) and which is further expanded upon in theme 3. This is an important challenge for practitioners to consider, given changes to nutritional intake mediated by cravings and external pressures can have implications on females' mental health and feelings of self, which may be tied to overall body dissatisfaction (Ryan et al, 2021).…”
Section: Theme 2: Sport Nutrition Practice Is Influenced By a Range O...mentioning
confidence: 57%
“…To be honest I've not gone out there across how many athletes on our programme and asked the question, as realistically is it important for me to know that? (Weight Restricted Sport Practitioner 1 -Female) This highlights how practitioners in high performance sport settings might also benefit from education as has been previously highlighted (Brown & Knight, 2022;Clarke et al, 2021), particularly given the well-established differences in nutritional regulation between the sexes and how this may also be influenced by menstrual and hormonal contraceptive cycles (Areta & Elliott-Sale, 2022). Beyond these perceptions, there was also a recognition that female ovarian health remains somewhat of a taboo subject in high performance sport settings.…”
Section: Theme 3: a Continuing Need For Ongoing Education And Further...mentioning
confidence: 91%
“…Further, it has been suggested that girls/women have a desire to be or may benefit from being coached by someone of the same gender (Diedrich, 2020;Ekholm et al, 2019), not least because being coached by an individual of the same gender means there is likely to be some common understanding and shared experience. However, recent evidence suggests that just because women coaches may share similar experiences as girls/women athletes, they are not always aware of research or evidence related to female-specific topics (i.e., menstruation), nor are their personal experiences the exact same as the individuals they may be coaching (Brown & Knight, 2022). Thus, it is positive to note women engaging with this program to increase their knowledge to improve engagement with girls in sport, even though they are the same gender.…”
Section: Discussionmentioning
confidence: 99%